The Effectiveness of Using Self-Video Recording towards Students’ Speaking Performance at MTsN 2 Solok - Luthfi Azhaar Driane; Merry Prima Dewi; Yuli Desnita (CV. Jendela Edukasi Indonesia, 2022)
This research aims to expose the effectiveness of using Self-Video Recording toward students’ speaking performance. There are several problems that had been found in this research. Firstly, students’ speaking scores were not satisfied yet. Secondly, students felt difficult to acquire foreign language speaking skills due to their insecurity and lack of confidence. This was descriptive-quantitative research. The population of this research was all the students in the 2nd grade of MTsN 2 Solok. The researcher applied the technique of purposive sampling to determine the sample which was class VIII-A and VIII-D included 56 students. Documentation was used as the method of data collection. Results indicated that self-video recording is very effective for teaching speaking English. The rating quality was very effective with a mean score of 83.69 and a proportion of students between 81-100%. Based on the result of the study, the self-video recording is very effective in teaching speaking in the 2nd grade of MTsN 2 Solok.